PERLINDUNGAN HUKUM TERHADAP DOSEN SWASTA DALAM MELAKSANAKAN PROFESINYA SEBAGAI TENAGA PENDIDIK DI INDONESIA - Permai Yud Yudi (JURNAL JUSTIQA, 2020)
Regarding the protection for teachers and lecturers not yet regulated in Law Number 14 of 2005 concerning teachers and lecturers in the seventh section concerning protection in article 39 it is explained that the government, regional government, community, professional organizations, and / or education units must provide protection against teacher and lecturer in the implementation of the task. Protection as referred to in paragraph (1) includes legal protection, professional protection, and protection of occupational safety and health.In addition to the Government Regulation on Teachers, the government issued new legal products relating to teaching staff namely Government Regulation No. 37 of 2009 concerning lecturers. The government regulation is more about the teaching profession regarding certification, rights, compulsory work and official ties, appointment, placement and transfer, sanctions, and others.This type of research conducted in this study is normative juridical research, namely by conducting an analysis of the problem through the study of legal norms contained in legislation in Indonesia and see the reality that occurs.The position of the lecturer is equal or equal to the foundation in accordance with the work agreement entered into by both parties. This position is clearly stated in the 1945 Constitution of the Republic of Indonesia, the Civil Code, and other regulations. This position can be seen from a legal and sociological point of view. The legal perspective can be seen in 2 (two) ways, namely: First, Preventive through agreements made before the lecturer works at the university; and Second, repressive through the Industrial Relations Court (PHI) institution in the event of disputes related to rights and obligations and this often comes from the lecturers because they are not protected by the profession they run.